RELIGIOUS EDUCATION PROGRAMMES AND MORAL DEVELOPMENT OF PRESCHOOL CHILDREN IN NAIROBI COUNTY, KENYA - Gatumu, Jane C.; Ndungu, Anne Wangari (Southeast Asia Early Childhood Journal, 2014)
This research study sought to find out how the different Religious education programmes offered by three religious groups (Christianity, Islam and Hinduism) in Kenya influenced the moral development of pre-school children in Nairobi County. The study was carried out in eight (8) religious schools which were a representation of three (3) religious groups: Christianity ((3 preschools), Islam (3 preschools) and Hinduism (2 preschools). The study was carried out within a period of three weeks in which the researchers found that each religious group had some unique contribution towards moral dimensions of the preschool children through its religious education programme. The study recommends a deliberate effort to actually teach children on how to be moral. The identities of the children and their preschools and religious affiliations were treated confidentially. Consent to observe children and have them listen to the stories was obtained from the parents/guardians/care-takers.